The Notch/Hes1 pathway sustains NF-κB activation through CYLD repression in T cell leukemia - Espinosa, Lluis (2010)
It was previously shown that the NF-κB pathway is downstream of oncogenic Notch1 in T cell acute lymphoblastic leukemia (T-ALL). Here we visualize Notch-induced NF-κB activation using both human T-ALL cell lines and animal models. We demonstrate that Hes1, a canonical Notch target and transcriptional repressor, is responsible for sustaining IKK activation in T-ALL. Hes1 exerts its effects by repressing the deubiquitinase CYLD, a negative IKK complex regulator. CYLD expression was found to be significantly suppressed in primary T-ALL. Finally, we demonstrate that IKK inhibition is a promising option for the targeted therapy of T-ALL as specific suppression of IKK expression and function affected both the survival of human T-ALL cells and the maintenance of the disease in vivo.